A mediation moderation conceptual model of inclusive leadership, psychological contract fulfilment and government support on total quality management–patient safety relationship - Koomson, Samuel (Journal of Psychological Perspective, 2022)
This paper aim to assess the direct effect of total quality management (TQM) on patient safety (PAT), exploring the mediating roles of inclusive leadership (ILD) and psychological contract fulfilment (PCF), and the boundary effect of government support (GOV). The paper develops a conceptual framework along with suppositions by integrating both empirical and theoretical literature in the fields of healthcare strategic management, leadership, industrial and organisational psychology and finance. This paper proposes that TQM will be positively related to PAT, and this positive relationship will be mediated by ILD and PCF. Additionally, government support (GOV) will moderate the direct positive effect of TQM on PAT. This paper provides implications for both researchers and practitioners in the areas of strategic decision-making in healthcare for enhancing PAT by applying TQM, ILD, PCF and GOV as strategic tools. It also provides implications for upcoming researchers to empirically test this conceptual framework in different healthcare settings.